ANALISIS RISIKO KEGAGALAN BISNIS PADA PERUSAHAAN TRANSPORTASI GO PUBLIC DI BURSA EFEK INDONESIA - Reza Septian Pradana (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
The study aims to identify the business failure of transportation firms go public in Indonesia Stock Exchange and analyze the factors that influent the business failure risk.The method used in this study is descriptive analysis and inference analysis using multiple regression. The data used in this study are business failure risk, current ratio (CR), and firm size of transportation firms go public in Indonesian Stock Exchange period 2017-2018.The result of analyzing annual financial report 30 transportation firms go public in Indonesia Stock Exchange period 2017-2018 is that 12 firms have negative profit in period 2017-2018. Based on calculating value of business failure risk, three firms which have the highest possibility to get business failure are APOL, CANI, and TAXI. The result of estimation using multiple regression shows that Current Ratio (CR) and firm size significantly influent to the business failure risk. Thus, transportation firms go public in Indonesian Stock Exchange need to enhance asset and and use equity more than debt for firm’s funding.